DAMAGE TOLERANCE EXPERIMENT AND ANALYSIS OF STIFFENED FUSELAGE PANEL WITH LONGITUDINAL CRACK - CHEN An; WEI YuLong; LIAO JiangHai; DONG DengKe (Jixie qiangdu)
Results from an experimental and analytical study of a curved stiffened aluminum panel subjected to combined internal pressure and axial tension loads are presented. The behaviors of the crack propagation and characteristics of the residual strength for fuselage panel are investigated. Stress intensity factors associated with different crack lengths are analyzed by using ANSYS software,and the crack propagation cycles are predicted. The residual strength curves are calculated based on the linear elastic fracture mechanics by comparison of experimental results. Analysis results agree well with the test results. Both results can provide the bases for the damage tolerance design and assessment of fuselage structure.